Identifying Cross-Sided Liquidity Externalities - Johannes A. Skjeltorp; Elvira Sojli; Wing Wah Tham (Norges Bank, 2012)
We study the relevance of the cross-sided externality of liquidity between market makers and takers from the two-sided market perspective and test the empirical implications of the Foucault, Kadan, and Kandel (2012) model. We use exogenous changes in the make/take fee structure and a technological shock for liquidity takers, as experiments to identify cross-sided complementarities between liquidity makers and takers in the U.S. equity market. We find positive cross-sided externalities between liquidity providers and takers. Using the estimate of the externality from the instrumental variable regression, we find that the loss in revenue due to the increased subsidization of liquidity demanders from a fee change in a trading venue exceeds the increase in trading rate and revenue from the positive cross-sided liquidity externality. Our findings highlight the importance of accounting for participation externalities in the pricing strategy of trading venues. Our findings also shed light on the way the order-posting behavior of market makers and takers is interrelated and contribute to the on-going policy debate on the maker/taker practices in U.S. equity markets.
hdl:11250/2496817
Keywords: G10; G20; G14; 330; liquidity cycle; liquidity externality; two-sided markets; make/take fees